Zero gas reference standards. Issue 15 (6th April 2016) - Miñarro, Marta Doval; Brewer, Paul J.; Brown, Richard J. C.; Persijn, Stefan; van Wijk, Janneke; Nieuwenkamp, Gerard; Baldan, Annarita; Kaiser, Claire; Sutour, Christophe; Macé, Tatiana; Škundrić, Nikola; Tarhan, Tanıl
Abstract : High purity nitrogen or air, often referred to as zero gas, is essential for calibrating instrumentation used in a wide variety of measurements, such as air quality monitoring. Abstract : High purity nitrogen or air, often referred to as zero gas, is essential for calibrating instrumentation used in a wide variety of measurements, such as air quality monitoring. Providing traceable and accurate quantification of impurities of the target component in zero gas is a major challenge, as the detection limits of appropriate analytical techniques are often close to the amount fraction of the measurand and accurate reference standards to underpin these measurements are yet to be developed. Purity analysis of zero gas is a significant contributor to the uncertainty budget and is compromised by a dependence on a zero reference for its realisation. This work describes state-of-the-art methods currently used to certify zero gas standards. We distinguish between absolute and relative techniques and provide guidance on calibration of the latter at trace amount fractions. Measurements to assess the performance of a selection of zero air generators and purifiers are also presented here.